Formation of foreign language professional information and communication competence of students (Eurasian Journal of Learning and Academic Teaching, 2023)
This article is devoted to the problem of student's foreign language communicative competence formation during their studies at the university, the approaches of foreign and Russian researchers to determine the content and structure of the competence. There is a brief characteristic of the concept of meaning "foreign language communicative competence". The article shows the necessity for the formation and improvement of foreign language communicative competence all together with its components. The methods of foreign language communicative competence formation are also shown in the article